"Living" Literature: A New Approach to Bibliographic Studies of Classical Literature (Wenxianxue). (2nd October 2021) - Guodong, Feng
Abstract: China's wenxianxue (bibliographic study of classical works) is an instrumental discipline centered on the methods and techniques of "working on documents." It provides reliable texts and materials for other disciplines, but also needs to give consideration to its own distinctive features and academic aspirations. Its research topics should focus on the documents themselves, rather than being confined to the methods and techniques of textual collation. Textuality, materiality, historicity, and sociality are the four most important elements of the literature, and the bibliographic study of classical literature should involve the holistic study of all four elements. If we analyze the historicity of the literature longitudinally and reveal its sociality horizontally, combining internal documentary research with research external to the documents, we may be able to attempt the creation of holistic research on "living" literature.